Pengaruh Suhu dan Lama Penyimpanan terhadap Kadar Vitamin C Infused Water Jeruk Lemon (Citrus Limon) - Dewi Nofita; Budi Setiawan (Journal Pharma Saintika, 2024)
Lemon is a fruit rich in vitamin C. Processing lemon as lemon infused water is one way to get the optimal benefits from lemon. Lemon infused water is processed by soaking it in water for several hours. Temperature and storage time are thought to affect the vitamin C levels of lemon. This study aims to determine the effect of temperature and storage time on the vitamin C levels of lemon infused water. This study used the lodimetry method with temperatures of 5°C, 10°C, 28℃C and storage times of 1,3,5 hours. Furthermore, the vitamin C levels of lemon infused water were analyzed. The results showed that temperature and storage time affected the vitamin C levels of lemon infused water (Citrus Limon). The higher the storage temperature of lemon infused water, the higher the vitamin C levels. The lower the storage temperature of lemon infused water, the lower the vitamin CC levels. The longer the storage, the lower the vitamin C levels of lemon infused water. Storage for 1 hour at a temperature of 28°C is the best time to obtain vitamin C levels. From the study, the vitamin C content of lemon infused water was 0.158% b/b.